Benchmarking of viral bronchiolitis management by general practitioners in the United Kingdom - Nickless, A; Galiza, E; Pollard, A; Drysdale, S (Mary Ann Liebert, 2017)
Viral bronchiolitis is the leading cause of hospitalization in infants in the United Kingdom (UK) with wide variation in rates of hospitalization in different geographical regions of the UK. A potential cause of these differences is variation in primary care management and referral to hospital. This study aimed to prospectively survey general practitioners (GPs) in the UK to provide a benchmark of practice against which future practice can be assessed. An electronic, structured questionnaire was sent to 1,001 geographically representative GPs in primary care centers in the UK, through the market research company MedeConnect, to assess their management of infants with viral bronchiolitis. We measured practice before the 2015 National Institute for Health and Care Excellence (NICE) bronchiolitis guideline against the guideline, to obtain a benchmark of practice. We also used a multivariate analysis to assess GP factors associated with variation in management. Thirty-nine percent of GPs did not refer to any guideline to manage infants with bronchiolitis, 33% did not routinely measure oxygen saturations, 48% prescribed an “inappropriate” (evidence of no benefit) medication, and 62% did not give written guidance to parents. GP factors influencing management included the year the GP qualified, sex, region of practice, and working at a dispensing practice. Up to 75% of GPs' management did not conform to the newly published 2015 NICE bronchiolitis guideline before its publication. There was wide variation in the management of infants with viral bronchiolitis by UK GPs. Most infants with viral bronchiolitis are not managed optimally by GPs and multiple GP factors influenced this management.